Developing a decision-support tool to inform blue nature-based solutions relying on kelp forest ecosystems - Casal, Gema; Pérez, Géraldine; O’Leary, Bethan C.; Taylor, Daisy; Sargent, Joseph; Hendy, Ian; Simide, Rémy; Cornet, Cindy C. (Frontiers in Environmental Science, 2026)
Nature-based Solutions (NbS) have emerged as a cost-effective and sustainable approach to address diverse societal challenges, including biodiversity loss and the impacts of climate change to enhance ecosystem resilience and community wellbeing. However, despite some advancements, the full potential of marine and coastal (blue) NbS relying on kelp forest ecosystems remains largely untapped, partly due to insufficient resources for selecting appropriate interventions and supporting their effective implementation. As the economic, ecological, and cultural significance of kelp ecosystems becomes increasingly recognised, there is a pressing need for enhanced management strategies to protect and restore these forests. The protection of kelp, will ensure the continued provision of their valuable goods and services. This study presents the Kelp Potential Blue Interventions Support tool (Kelp PBI-Support), which uses a hierarchical tree structure to offer NbS implementation recommendations specifically adapted to kelp ecosystems and the context in which they are to be implemented. This tool enables the planification and design of blue NbS relying on kelp forest ecosystems and contributes to addressing societal challenges of climate change mitigation and adaptation. By adopting an evidence-based approach and incorporating expert knowledge, the Kelp PBI-Support acts as a decision-support system, providing standardised and customised recommendations for a range of potential interventions in kelp forest ecosystems tailored to meet the specific needs of each user. The utility of the tool is demonstrated through a case study of the Isle of Wight, located in the South of England, United Kingdom. Here, the recent designation of the area as a UNESCO Biosphere Reserve offers a strategic opportunity to improve the management of kelp forests and other marine and coastal ecosystems present to help address the societal challenges the island is facing. In this context, PBI-Support has been applied to showcase how it can inform and guide ecosystem management efforts.